Spatial Variability of Heavy Metals in Native Oysters From an Anthropogenically Impacted Estuary in Northeastern Brazil - Senez-Mello, Thaise Machado; Crapez, Mírian Araújo Carlos; Ramos e Silva, Carlos Augusto; da Silva, Eduardo Teixeira; da Fonseca, Estefan Monteiro (Frontiers in Marine Science, 2020)
This brief research compares the bioconcentration of heavy metals (Cd, Cr, Cu, Pb, Ni, and Zn) in the soft tissues of native oysters Crassostrea rhizophorae (Guilding, 1828) from two areas in the Potengi estuary, northeastern coast of Brazil. The purpose was to test the hypotheses of relevant differences in bioaccumulation while the environmental conditions change upstream. The downstream station showed higher concentrations for cadmium and nickel, while the upstream one, revealed increased values for body weight, condition index, chromium, lead, and zinc (p < 0.05). The cooper variation between sites was negligible, but, as for zinc and chromium, the metal content observed was above guidance levels. Results revealed two aspects that were mainly influencing the bioavailability and bioaccumulation of metals in oysters. Firstly, the predominance of marine or riverine characteristics of each site, and secondly, the relative proximity to the point of introduction of the pollutant, even though stations were not quite far apart. Crassostrea rhizophorae accumulated heavy metals in significant concentrations, endorsing its efficiency as a biomonitor.